Stardust family - Poroyama, Aki (Yen Press, 2025)
"In the midst of a declining birth rate and rampant reports of child abuse, Japan has required prospective parents to pass a test for the right to conceive. The test's evaluators are children themselves, deliberately behaving badly to provoke couples into an aggressive response and disqualify them on the spot. Hikari is one such evaluator in this system, and he thinks he's seen it all- that is, until he's assigned to the Hirokawa family..."--